Effects of web-based palliative wound care education using the clinical judgment model: A quasi-experimental study with facilitylevel random allocation - Sung Ok Chang; Dayeong Kim; Young-Rim Choi; Dai-Young Kwon; Ye-Na Lee (Journal of Korean Gerontological Nursing, 2026)
Purpose: Nursing homes face a growing demand for high-quality palliative wound care. Nursing home staff require not only knowledge but also clinical judgment to address the complex needs of residents at the end of life. This study aimed to develop and evaluate a web-based palliative wound care education program using a clinical judgment model. Methods: An educational program was developed using the ADDIE model through needs analysis with 10 nursing home staff, program design and development, and pilot implementation and evaluation. Program effectiveness was evaluated in a quasi-experimental study with facility-level random allocation. Four nursing homes were randomly allocated to the experimental or control condition, and 52 nursing home staff were included in the final analysis (n=26 per group). The experimental group received clinical judgment model-based web education, whereas the control group received general web-based palliative wound care education without the clinical judgment model. Clinical judgment was assessed before and after the intervention using nonparametric tests. Results: Both groups showed significant improvements in clinical judgment. However, the experimental group demonstrated greater improvements than the control group in noticing (Z=-3.91, p